53 Risk factors for facial lesions in piglets and teat injuries in sows – a review - Chou, Jen-Yun (J Anim Sci, 2020)
Painful procedures performed on piglets are one of the most important welfare concerns of intensive pig production. For example, teeth resection is a common practice whereby the canine (needle) teeth are clipped or ground to prevent piglet facial and sow teat lesions. Based on a global consumer survey in 2018, 60% of respondents will potentially stop purchasing pork from pigs experiencing painful procedures. In contrast to tail docking and surgical castration, little is known about the risk factors for piglet facial and sow teat lesions and therefore the need for teeth resection. We reviewed the literature to better understand these risk factors and conducted a survey to identify preventative strategies in practice that have enabled producers to avoid teeth resection. For the literature review, we used Web of Science and Google Scholar to include peer-reviewed publications and gray literature. The questionnaire was distributed with convenience sampling to relevant stakeholders. In the questionnaire, information on current on-farm practices regarding teeth resection was collected, including the method, frequency, and reason for conducting teeth resection, and preventative measures used. Preliminary findings of the literature review showed that most studies only focused on teeth resection and its effect on piglet facial and sow teat lesions. Other risk factors identified are litter size, farrowing system and flooring, milk production, management of fostering, flooring, and enrichment. The survey is ongoing and the complete results will be presented during the conference. Our review suggests many risk factors are related to piglet facial and sow teat lesions other than whether or not teeth resection is carried out. There is still a knowledge gap in the understanding of how alleviating these risk factors can prevent said lesions, and further research and dissemination of best practice is needed to explore different solutions instead of solely relying on teeth resection.